A Proposed Program Based on the Japanese Approach to Develop Understanding of Socioscientific Issues and Critical Thinking Skills in Teaching Biology for Secondary School Students - Al-Nufaie, Nasser Qutaym (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to develop a program based on the Japanese approach to enhance the understanding of socio-scientific issues and critical thinking skills in teaching the biology curriculum at the secondary level in the Kingdom of Saudi Arabia. The study adopted a descriptive-analytical methodology, and the research tool consisted of a list of standard specifications that should be considered in building the program. The biology curriculum for the third year of secondary school was selected as the study sample. The study resulted in a list of 75 standard specifications required for constructing the program, distributed across five domains: objectives (13 specifications), content (13 specifications), teaching and learning strategies (12 specifications), educational activities (17 specifications), learning resources (9 specifications), and assessment (11 specifications). Based on these specifications, the program grounded in the Japanese approach was constructed. In light of the study findings, the researcher recommended:1- Employing the Japanese approach in teaching socio-scientific issues and enhancing critical thinking skills in the biology curriculum at the secondary level.2-Addressing socio-scientific issues in the third-year secondary biology curriculum from scientific, legal, ethical, and social perspectives.3- Identifying the development of critical thinking skills as a primary objective in the third-year secondary biology curriculum and integrating them with socio-scientific issue topics.4-Conducting a study to apply the developed program in teaching the biology curriculum at the secondary level. 5- Designing a program based on the Japanese approach to enhance other variables such as prediction skills, decision-making, and ethical values related to socio-scientific issues.